ANALISIS CRITICAL SUCCESS FACTORS DALAM MENILAI KINERJA LAYANAN YDSF SURABAYA - Suwanto, Indra (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to analyze and to find out how great the influence of Critical Success Factors in assessing service performance at Yayasan Dana Sosial Al Falah Surabaya. Qualitative method is carried out in this research as the research method. The indicators of the Critical Success Factors in this research are: service quality, community satisfaction, and productivity. The result of the discussion is that service quality is assessed by using Community Satisfaction Index value is calculated by using the weighted average value based on the decree of State Minister of Empowerment of State Apparatus Number: KEP/25/M.PAN/2/2004 each public service element at YDSF. The result of index score is 3.21 and the converted community satisfaction index score is 80.25 which are the category of good service quality. The result shows that there is a good improvement of performance. Productivity uses two standards for i.e.: manpower productivity and machine productivity. The average of manpower productivity in 2011 is 2004.55 and the average of manpower productivity in 2012 is 2091.84, it is considered to be quite good since each year the employees can increase their services in serving the donors and community. While the average of machine productivity (computer) in 2011 is 55.125 and the average of machine productivity (computer) in 2012 is 57.526. it can be considered to be quite good since each year the object which is served increases so it can work efficient and effectively.Keywords: Service Quality, Community Satisfaction, and Productivity Level